Meningkatkan Partisipasi Pemilih dalam Pemilu 2024: Pendekatan Stakeholders Mapping Analysis - Denny Iswanto; Dewi Bayu Pamungkas (Jurnal Adhyasta Pemilu, 2023)
The main objective of this study is to map out the various stakeholders involved in the 2024 Elections as a proactive measure aimed at significantly enhancing the political participation of the community. Conducted using qualitative research methodology, this study focuses on the collection and analysis of secondary data to generate accurate and relevant information about the involved stakeholders. The mapping results reveal the distinct and crucial roles played by different entities in the election process. The central and regional governments serve as 'contest setters', establishing the context and rules for the elections. Then, there are the General Election Commission (KPU), Election Supervisory Agency (Bawaslu), Non-Governmental Organizations (NGOs), media, and political parties, all acting as 'Players'. Furthermore, the officially nominated candidates and running mates are the main subjects of the election, designated as 'Subjects', while the general voting population is categorized as the 'Crowd'. These findings provide significant and in-depth insights into the dynamics and structure of stakeholders in the 2024 Elections, proving crucial for planning and implementing effective policy strategies designed to boost the political participation of the community.